Physicochemical properties of bean pod (Phaseolus vulgaris) flour and its potential as a raw material for the food industry (2020)
ABSTRACT: The sustainable development of agro-industry requires the efficient use of all raw matters, which implies physicochemical and functional studies of by-products for finding their potential usage in industrial processes. The objective of the present study was to assess some physicochemical and functional properties of fIour obtained from the bean pod. Two types of drying methods were tested: convection and vacuum. The fIours tended to yellow color according to b* parameter values (convection drying: 17.54; vacuum drying: 18.35), with a slight red hue. They also showed high water holding (convection drying: 8.30 g g-1; vacuum drying: 7.56 g g-1) and oil holding capacity (convection drying: 2.53 g g-1; vacuum drying: 2.56 g g-1), polyphenols content (convection drying: 26.62 mg GAE g-1 DW; vacuum drying: 3.77 mg GAE g-1 DW) and antioxidant capacity (convection drying: 33.42 µmol Trolox g-1; vacuum drying: 5.27 µmol Trolox g-1). The results were similar for the two types of drying methods, except for the antioxidant capacity. Since convection drying is more economical and available than vacuum drying, only the fIour obtained by convection method was analyzed on compositional and structural characteristics. This fIour showed to be a good source of dietary fiber (66.93%), being the insoluble fiber the predominant fraction (59.97%). Moreover, a high content of ash (6.65%) and low lipid content (0.58%) were also found. The IR spectrum showed signs corroborating the presence of dietary fiber, which also was evidenced morphologically. Overall, the results obtained indicated that the bean pod fIour obtained by convection drying has potential use as a raw material for the food industry.